2016
DOI: 10.1016/j.jmva.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Supervised singular value decomposition and its asymptotic properties

Abstract: a b s t r a c tA supervised singular value decomposition (SupSVD) model has been developed for supervised dimension reduction where the low rank structure of the data of interest is potentially driven by additional variables measured on the same set of samples. The SupSVD model can make use of the information in the additional variables to accurately extract underlying structures that are more interpretable. The model is general and includes the principal component analysis model and the reduced rank regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Then model (1.4) can be written in a more compact matrix form: (1.5) We treat the loadings G(X) and Γ as realizations of random matrices throughout the paper. This model is also closely related to the supervised singular value decomposition model, recently studied by Li et al (2015). The authors showed that the model is useful in studying the gene expression and single-nucleotide polymorphism (SNP) data, and proposed an EM algorithm for parameter estimation.…”
Section: This Papermentioning
confidence: 99%
“…Then model (1.4) can be written in a more compact matrix form: (1.5) We treat the loadings G(X) and Γ as realizations of random matrices throughout the paper. This model is also closely related to the supervised singular value decomposition model, recently studied by Li et al (2015). The authors showed that the model is useful in studying the gene expression and single-nucleotide polymorphism (SNP) data, and proposed an EM algorithm for parameter estimation.…”
Section: This Papermentioning
confidence: 99%
“…Our ProPrPCA‐Krige model is closely related to the SupSVD model recently proposed by Li, Yang, Nobel, and Shen (). The SupSVD model is expressed as bold-italicX=bold-italicUbold-italicVsans-serifT+bold-italicE where U = YB + F .…”
Section: Probabilistic Predictive Pcamentioning
confidence: 97%
“…The SupCP model specified in Section 3.1 reduces to traditional factor analysis without supervision (B = 0) and when K = 1, i.e., when X is a matrix. More generally, when K = 1 SupCP reduces to the SupSVD model [19]. Thus, an alternative strategy of decomposing X is to apply SupSVD to the matricized data X (1) .…”
Section: Special Casesmentioning
confidence: 99%